IDENTIFICATION OF PATHOGENIC BACTERIA OF SELAIS (Ompok hypopthalmus) ARE CAUGHT IN THE KAMPAR RIVER TERATAK BULUH VILLAGE IN RIAU PROVINCE - Saragih, Andre A; Syawal, Henni; Lukistyowati, Iesje (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research had been conducted in April up to June 2014 in LaboratoryofParasite andFish Diseases,Faculty of Fisheriesand Marine Sciencesof RiauUniversity. This research aims to find out the type of bacteria pathogenicpotentially infect slice of fish in the Kampar River, Teratak Buluh Village in RiauProvince. The adventages of this research is to provide the types of bacterialpathogens that potentially attack the slice of fish in the public water of Riau. Themethod applied in this research is survey methode by taking some samples in thefield ( in Kampar River ) and then analyzed in the laboratory. And the result isthere are five species of bacteria found namely Aeromonas sp, Basillus sp,Pseudomonas sp, Stapyhilococcus sp, and Edwardsiella sp.Keywords: Bacterial pathogens, Fish slice